Design of wavelength rotation graph model applied in wavelength switching optical network - ZHAO Ji-jun1; ZHANG Shu-guang1; ZHAO Wen-yu2 (Tongxin xuebao)
Based on distributing uniformly virtual network topology links and associated wavelengths to the surface of rotating sphere,a new wavelength rotation graph model of wavelength switching optical network（WSON） was constructed,and a creative method to solve the routing and wavelength assignment（RWA） problems was proposed.The simulation results show that if the wavelength number of each link is set separately to 4 and 8,the average blocking probability of the RWA based on the rotation graph model reduces by 5.03% and 9.71%,and the average resource utilization increases by 3.3% and 1.54% respectively,as compared with the existing model.This method would be useful for solving the problem of optical network RWA which has wavelength conversion capabilities.